2011
DOI: 10.1073/pnas.1018266108
|View full text |Cite
|
Sign up to set email alerts
|

Parallel adaptive feedback enhances reliability of the Ca 2+ signaling system

Abstract: Despite large cell-to-cell variations in the concentrations of individual signaling proteins, cells transmit signals correctly. This phenomenon raises the question of what signaling systems do to prevent a predicted high failure rate. Here we combine quantitative modeling, RNA interference, and targeted selective reaction monitoring (SRM) mass spectrometry, and we show for the ubiquitous and fundamental calcium signaling system that cells monitor cytosolic and endoplasmic reticulum (ER) Ca 2+ levels and adjust… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
38
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 43 publications
(42 citation statements)
references
References 32 publications
(23 reference statements)
3
38
1
Order By: Relevance
“…SR Ca 2+ levels were directly measured using T1ER as previously described (Abell et al, 2011; Tsai et al, 2014). See Extended Experimental Procedures for a more detailed protocol.…”
Section: Methodsmentioning
confidence: 99%
“…SR Ca 2+ levels were directly measured using T1ER as previously described (Abell et al, 2011; Tsai et al, 2014). See Extended Experimental Procedures for a more detailed protocol.…”
Section: Methodsmentioning
confidence: 99%
“…8). To be consistent with parallel adaptive feedback, the tcSR of mdx muscle must have a lower [Ca 2ϩ ] than that in WT to induce an increase in PMCA protein expression and the lSR must maintain a [Ca 2ϩ ] that is similar in mdx and WT muscle to maintain a similar expression level of the SR Ca 2ϩ pump (1,8). A lower [Ca 2ϩ ] in the tcSR of mdx muscle is probably the result of the leaky Ca 2ϩ release channel on the tcSR (2).…”
Section: Stim1 Isoforms In Musclementioning
confidence: 97%
“…It has been demonstrated that cells can continue to transmit signals correctly in the presence of higher or lower than normal resting [Ca 2ϩ ] and expression levels of the major Ca 2ϩ signaling proteins. Feedback mechanisms detect the [Ca 2ϩ ] of the external environment, cytoplasm, and internal Ca 2ϩ store, and protein expression levels of STIM1, PMCA, and the SR Ca 2ϩ pump are adapted in parallel (1). Evidence for a similar situation involving the Na ϩ -K ϩ ATPase, PMCA, SR Ca 2ϩ pump, and Na ϩ /Ca 2ϩ exchanger has been put forward from work in smooth muscle cells (28 (1), an increase in cytoplasmic [Ca 2ϩ ] will increase the expression of PMCA (Fig.…”
Section: Stim1 Isoforms In Musclementioning
confidence: 99%
See 1 more Smart Citation
“…Consolidated evidence, as well as recent evidence, indicates that this group of proteins, with the mission to keep tight control of free Ca 2ϩ concentration, is in turn subjected to regulation by several mechanisms controlled by changes in free Ca 2ϩ concentration. In some cases, these self-regulatory processes involve parallel compensatory changes in several Ca 2ϩ regulatory proteins so that increases or decreases in intracellular stores and cytosolic Ca 2ϩ levels slowly adjust the concentrations of key signaling pathway components (3). In other cases, components of the homeostasis machinery are coordinately modified to respond to chronic pathological conditions as in end stages of heart failure (4,5) or in neurodegenerative processes.…”
Section: Intracellular Free Camentioning
confidence: 99%